Voicing the Unvoiced: Fighting propaganda in Laurie Halse Anderson’s Speak - Fălăuș, Anamaria (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales)

(untitled) (Département de communication sociale et publique, Université du Québec à Montréal, 2025)
Laurie Halse Anderson’s novel Speak explores a young girl’s journey through the aftermath of sexual assault, delving into themes of trauma and recovery while also critiquing various forms of propaganda and their impact on the protagonist, Melinda Sordino. This analysis examines how Anderson uses school policies, social dynamics, and media representation to portray the mechanisms of control and influence that shape Melinda’s environment and suppress her voice. By deconstructing these elements, this study uncovers the pervasive nature of propaganda and its role in reinforcing societal norms and expectations.